TO STUDY EFFECTIVENESS OF DIFFERENT ANALGESIC DRUGS FOR LABOUR ANALGESIA IN OBSTETRICS AND GYNAECOLOGY DEPARTMENT OF TERTIARY CARE HOSPITAL - Dr Alpana Sahu; Dr Virendra Kushwaha; Dr Pooja Agrawal; Dr Renu Gupta; Dr Amit Kumar; Dr Himanshu Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Labour pain is considered one of the most intense types of pain, necessitating effective pain management techniques to ensure maternal comfort and safety. Various analgesic drugs are available, but their efficacy can vary, particularly during labour. This study aims to assess the effectiveness of different analgesic drugs used for labour analgesia in a tertiary care hospital. The main objectives of this study were to evaluate the demographic profile of the study subjects, compare the effectiveness of different analgesic drugs for labour analgesia. Materials & Methods: A prospective observational study was conducted involving 148 pregnant women admitted with labour pain in the obstetrics and gynaecology department at GSVM medical college, Kanpur. The study participants received analgesic drugs, diclofenac with epidosin, tramadol with epidosin, and anafortan. pain relief was measured using the visual analogue scale (vas). Results: All drugs significantly reduced pain, with VAS scores dropping from 10 to 6 after administration. The duration of the first stage of labour was decreased. Pregnant women receiving tramadol along with epidosin, in primigravida,72.22% of were in age 19-24 years and 27.7% in 25-29 years. In multigravida, 33.3 % in age 19-24 years and 66.6% in 25-29 years. Pregnant women receiving, anafortan, in primigravida, 67.44% were in age 19-24 years and 32.55% in 25-29 years. In multigravida, 20% were in age 19-24 years, 65.71% in 25-29 years and 14.28% in 30-34 years. Conclusion: These analgesics were effective in labour pain management, showing equal effectiveness.